PENGARUH MOBILE LEARNING FLIPBOOK TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SEJARAH DI SMAN 2 TAKALAR - Nurfadilla Adelia; Andi Syukri Syamsury (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
A flipbook is a book in the form of a digital file, where readers can open the flipbook page by page just like reading a book that can be accessed anytime and anywhere. This research aims to determine the effect of Mobile Learning Flipbook on learning outcomes in history subjects at SMAN 2 Takalar. The type of research used in this research is a pre-experiment one-group pre-test post-test design. This research data was collected using a multiple choice test which was given twice, namely before the treatment was given (pre-test) and after the treatment was given (post-test). So based on the results of data analysis, researchers know that there is an increase in history learning outcomes using Mobile Learning Flipbook. The results of this research show that in the first cycle it shows that the average score of 26 students, namely 58.80%, has not been classically met, while in the second cycle it shows that the average score of 26 students, namely 80%, has fulfilled the KKM and classically has been fulfilled. . The significant level = 0.05 and the degree of freedom (dk) = 25 from the distribution table obtained t-table = 1.708 with the calculation results of t-count > t-table 10.942 > 1.708, thus H0 is rejected and H1 is accepted. This shows that there is an influence of use of Mobile learning Flipbook on student learning outcomes in the History subject class XI SMAN 2 Takalar.